A new intelligent group elevator control approach - Baygin, Mehmet; Karakose, Mehmet (My University, 2012)
Given the structure of urbanization, the use of elevator has become a necessity. The increase of population density in buildings in parallel to the structure of urbanization has led to the emergence of a group controlled elevator systems. In general, the group elevator system is intended to reduce the average waiting time of passengers and provide energy efficiency. For these purposes, in this study, optimization for group elevator systems and a group of estimation based control algorithm has been realized. In a recent study, the artificial immune system, genetic algorithm, and DNA has been used as optimization algorithms, again an estimation algorithm has been proposed for the group controlled elevator systems. The results obtained from system optimization and estimation algorithm are evaluated with fuzzy system and the most appropriate technique is determined. © 2012 CZECH TECH UNIV.
15th International Conference on Mechatronics, MECHATRONIKA 2012 -- 5 December 2012 through 7 December 2012 -- Prague -- 95657
Keywords: estimation; fuzzy system; group controlled elevator systems; optimization algorithms